2007
DOI: 10.1007/s11199-007-9309-y
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of the Recruiting of Men and Women for Sales Positions in Turkey

Abstract: This study examines the effects of gender on recruitment of salespeople in Turkey, an emerging economy with a male-dominated society where historical and cultural values have frequently limited women's employment opportunities. Based on 16 interviews with male and female recruiters from four industries actively hiring productive salespeople, the study addresses gender effect on recruiting of men and women for sales positions in Turkey. The findings of this qualitative study provide an opportunity to expand our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Although quantitative research clearly dominates the field of personnel selection, a general trend can be discerned in management/industrial and organizational psychology, that is qualitative articles are becoming more common (Bluhm, Harman, Lee, & Mitchell, 2011; for examples in the selection field, see König, Jöri, &Knüsel, 2011, andPinar, Eser, &Hardin, 2007). The attractiveness of qualitative approaches lies in their ability to generate rich data, unique insights, and new theoretical arguments (Lee, Mitchell, & Sablynski, 1999).…”
Section: Grounded Theory: An Overviewmentioning
confidence: 99%
“…Although quantitative research clearly dominates the field of personnel selection, a general trend can be discerned in management/industrial and organizational psychology, that is qualitative articles are becoming more common (Bluhm, Harman, Lee, & Mitchell, 2011; for examples in the selection field, see König, Jöri, &Knüsel, 2011, andPinar, Eser, &Hardin, 2007). The attractiveness of qualitative approaches lies in their ability to generate rich data, unique insights, and new theoretical arguments (Lee, Mitchell, & Sablynski, 1999).…”
Section: Grounded Theory: An Overviewmentioning
confidence: 99%
“…A recent study by Pınar, Eser and Hardin (2007) provided some insights into the gender effect on the recruitment of salespeople in Turkey. These insights are: (1) there is no apparent or noticeable recruiter-recruit gender effect (or bias) on recruiting decisions for sales positions in the industries that were studied.…”
Section: Women In the Turkish Economymentioning
confidence: 99%
“…Both male and female recruiters seem to prefer female applicants because of their expected selling effectiveness. In addition, Pınar et al (2007) found that target-market gender had a mixed effect on the selection of applicants. In some cases, female applicants were selected regardless of the gender of the target market.…”
Section: Women In the Turkish Economymentioning
confidence: 99%
“…• The gender pay gap (Akder, 2003;Kasnakoglu & Dayioglu, 1997;Pinar, Eser, & Hardin, 2007). • Perhaps also a discouraged worker effect.…”
Section: Introductionmentioning
confidence: 99%